COMBINATION OF HEDYOTIS CORYMBOSA L. AND TINOSPORA CRISPA ETHANOLIC EXTRACT INCREASE CISPLATIN CYTOTOXICITY ON T47D BREAST CANCER CELLS - Rollando, Rollando (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Ursolic acid was a compound found in Hedyotis corymbosa L., (HCoL) while berberine found in Tinospora crispa (TCa) which are proven to have cytotoxic effect to cancer cells. This research aims to review the effect of cisplatin, ethanolic extract of HCoL and TCa to the sensitivity increase on breast cancer cells, which will be confirmed through apoptosis induction and cell cycle modulation. Methods: The cytotoxic effect was tested using 3-(4,5-dimethylthiazol-2-il)-2,5-diphenyltetrazolium bromide assay on T47D cell using the IC50 parameter. The combination was tested by determining their combination index (CI) and cell viability. The combination effect of apoptosis induction and cell cycle modulation was observed using flow cytometry method. Results: The cytotoxic test result of the combination shows CI value of below 1 at the concentration of HCoL ethanolic extract as much as 1 Î¼g/mL, TCa ethanolic extract as much as 6 Î¼g/mL, and cisplatin as much as 2,5 Î¼M. The combination of HCoL ethanolic extract, TCa ethanolic extract, and cisplatin results in phase S cell accumulation (29.98%) on breast cancer cell T47D and was able to induce apoptosis. Conclusion: The result proves that ethanolic extract of HCoL and TCa can be developed as a cochemotherapeutic agent with cisplatin to increase the effectivity of breast cancer treatment.